The relation between aortic arch branching types and the location of large vessel occlusion in cardioembolic stroke. (July 2021) - Xu, Lu; Liao, Juan; Liu, Li; Zhao, Li-Bo; Liu, Shu-Dong; Chen, Yu; Tang, Ge; Wang, Juan; Chen, Dan; Liu, Ting; Zhou, Ting; Zhou, Zhen-Hua; et al.
Highlights: There is a growing tendency for the percentage of left-sided cardioembolic strokes with advancement of the aortic arch types. The left–right propensity of cardioembolic stroke is related to the proximity of clot lodging in different aortic arch types. Abstract: Cardiac embolism is the leading etiology of ischemic strokes. There are arguments about the left–right propensity of cardioembolic strokes. This study aimed to reveal the relationship between the different aortic arch types and the location of large vessel occlusion (LVO) in cardioembolic stroke. We retrospectively identified all patients with acute ischemic stroke admitted to our comprehensive stroke center who had medium- to high-risk cardioembolic sources according to the TOAST classification. Only those with LVO and available images of the aortic arch were included. Patients were classified into 3 groups according to the aortic arch types: Type I (n = 44), Type II (n = 105), Type III (n = 36). The thrombus was divided into large thrombus or small thrombus based on the location of LVO. Overall, left-sided strokes (50.8%) were almost equal to right-sided (49.2%). There was a growing tendency for the percentage of left-sided infarcts with advancement of the aortic arch types either in the total cases or in the atrial fibrillation cases, with no statistical difference between the 3 aortic arch types. In type III aortic arch, left-sided strokes (69.0%) were twice than right-sided (31%) in large thrombus (P < 0.05), while right-sided strokes (85.7%) were more common than left-sided (14.3%) in small thrombus (P < 0.05). Conversely, in type Ⅰ and II aortic arches, left-sided strokes were more common than right-sided in small thrombus, while right-sided strokes were more common than left-sided in large thrombus (P < 0.05). The left–right propensity of cardioembolic stroke is related to the proximity of clot lodging in different aortic arch types.